Changes in government spending on healthcare and population mortality in the European union, 1995–2010: a cross-sectional ecological study. (December 2015) - Budhdeo, Sanjay; Watkins, Johnathan; Atun, Rifat; Williams, Callum; Zeltner, Thomas; Maruthappu, Mahiben
Objective: Economic measures such as unemployment and gross domestic product are correlated with changes in health outcomes. We aimed to examine the effects of changes in government healthcare spending, an increasingly important measure given constrained government budgets in several European Union countries. Design: Multivariate regression analysis was used to assess the effect of changes in healthcare spending as a proportion of total government expenditure, government healthcare spending as a proportion of gross domestic product and government healthcare spending measured in purchasing power parity per capita, on five mortality indicators. Additional variables were controlled for to ensure robustness of data. One to five year lag analyses were conducted. Setting and Participants: European Union countries 1995–2010. Main outcome measures: Neonatal mortality, postneonatal mortality, one to five years of age mortality, under five years of age mortality, adult male mortality, adult female mortality. Results: A 1% decrease in government healthcare spending was associated with significant increase in all mortality metrics: neonatal mortality (coefficient −0.1217, p  = 0.0001), postneonatal mortality (coefficient −0.0499, p  = 0.0018), one to five years of age mortality (coefficient −0.0185, p  = 0.0002), under five years of age mortality (coefficient −0.1897, p  = 0.0003), adult male mortality (coefficient −2.5398, p  = 0.0000) and adult female mortality (coefficient −1.4492, p  = 0.0000). One per cent decrease in healthcare spending, measured as a proportion of gross domestic product and in purchasing power parity, was both associated with significant increases ( p  < 0.05) in all metrics. Five years after the 1% decrease in healthcare spending, significant increases ( p  < 0.05) continued to be observed in all mortality metrics. Conclusions: Decreased government healthcare spending is associated with increased population mortality in the short and long term. Policy interventions implemented in response to the financial crisis may be associated with worsening population health.